Failure Mode of Deep-Buried Rectangular Chamber and Upper Bound Solution of Surrounding Rock Pressure - Daobing Zhang; Linhai Zeng; Zhilin Lv; Xiaochuan Yu; Chang Liu; Anming Jiang; Xianyong Jiang; Qi Li; Yongxiang Yang (Mathematics)
In order to obtain more reasonable failure modes and more precise surrounding rock pressures of deep-buried underground rectangular chambers, the failure mode of a “wedge-shaped collapse body + arc rotator + logarithmic spiral rotator” deep-buried chamber is constructed based on the analysis of existing failure mode. The upper bound solution of the surrounding rock pressure is derived based on limit analysis. The validity of the proposed failure model and the reliability of the limit analysis approach are demonstrated through numerical simulations, theoretical verification, and comparisons with engineering practices. The influence of various parameters on surrounding rock pressure is analyzed. The results show that each parameter has different influence on the surrounding rock pressure. The surrounding rock pressure q and e increases linearly with the increase in rock gravity γ and chamber size, and decreases with the increase in cohesion c and internal friction angle φ. The surrounding rock pressure q decreases with the increase in lateral pressure coefficient K, while surrounding rock pressure e increases with the increase in lateral pressure coefficient K.